A super amphiphilic carbon and its preparation method and application
By pyrolyzing wood powder and tetrafluoroboric acid ionic liquid in an inert atmosphere, stable and low-cost super-parent carbon was prepared, which solved the problem of high and unstable preparation cost of super-parent carbon materials in the prior art, and realized Pickering High-efficiency reaction effect in emulsion catalysis.
Patent Information
- Application Number
- CN202211255151.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-13
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2042-10-13
AI Technical Summary
It is difficult to effectively prepare stable and low-cost super-parent carbon materials in the prior art, and the existing super-parent carbon is unstable under aerobic conditions, which affects its application in Pickering emulsion catalysis.
Mix wood powder with an ionic liquid containing tetrafluoroboric acid anion and pyrolyzed in an inert atmosphere to prepare a carbon material with super hydrophilic and super lipophilic properties, and improve the microdomain composed of boron oxygen bonds and fluorine elements. Material stability.
The preparation of super-parent carbon is achieved at low cost, improving the stability of the material and the reaction efficiency in Pickering emulsion catalysis, especially in the oil-water system to form stable emulsions and improve the catalytic reaction efficiency.
Smart Images

Figure CN115557485B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a super amphiphilic carbon and to a preparation method and application of the super amphiphilic carbon, belonging to the field of carbon material modification and Pickering emulsion catalysis. Background Art
[0002] The wettability of particle surfaces is an important physical and chemical property of solid materials. When the surfaces of materials become superhydrophilic or superhydrophobic, they can be widely used in many aspects such as oil-water separation process, self-cleaning glass and textiles. Furthermore, if a material surface can show both superhydrophilic and superoleophilic properties, we call this material a superamphiphilic material.
[0003] Designing superwetting surfaces to improve reaction efficiency is one of the focuses of catalytic chemistry. In liquid-liquid two-phase catalysis, colloidal particles are used instead of surfactants to promote the formation of an emulsion in a water-oil two-phase system, which is called a Pickering emulsion. The wettability of the solid particle surface has a great influence on the formation and stability of the Pickering emulsion. Generally, hydrophilic particles (such as SiO2) can stabilize water-in-oil emulsions, while lipophilic particles (such as carbon black) can be used to stabilize oil-in-water emulsions, but it is rare for solid particles to stabilize both oil-water emulsions and oil-oil emulsions. Superamphiphilic materials have both superhydrophilicity and superlipophilicity, which is expected to further improve the stability of Pickering emulsions, thereby improving the efficiency of catalytic reactions in Pickering emulsions. Since superamphiphilic materials are not easy to prepare, their application in Pickering emulsion catalysis has rarely been reported.
[0004] Since the hydrophilic and lipophilic chemical groups are different, it is difficult to achieve super-amphiphilic properties on the surface of the same material. Among solid particles, carbon materials are widely used in many fields due to their high chemical and thermal stability. In order to obtain super-amphiphilic carbon materials, the prior art involves spraying a hydrophilic graphene oxide solution onto a hydrophobic sulfur-nitrogen co-doped graphene to form an aerogel (such as CN108439373A "an amphiphilic Janus structure graphene-based aerogel and its preparation method"); or modifying hydrophilic and hydrophobic groups onto carbon nanotubes or polymers at the same time (such as CN107174972A "a super-amphiphilic porous membrane material and its preparation method and application"; another example is CN104383899A "a hydrophilic oil-absorbing cotton"); and graphite powder is further oxidized by hydrogen peroxide to improve the hydrophilicity of carbon by electrochemical oxidation (such as CN101468796 "a preparation method and product of quantized carbon material liquid and its preparation equipment"). From the existing methods for preparing super-amphiphilic carbon, some methods are complicated, and some methods need to use high-value-added graphene oxide or carbon nanotubes as raw materials.
[0005] The Chinese patent in which the first inventor of the present application is the main inventor discloses "a super-amphiphilic carbon and its preparation method and application (CN112794303A)". The wood powder is mixed with an ionic liquid containing a bistrifluoromethanesulfonyl imide anion, and then pyrolyzed in an inert atmosphere to obtain a nitrogen-doped super-amphiphilic carbon. This carbon can effectively promote related liquid-liquid catalytic reactions. Simultaneously constructing hydrophilic and lipophilic micro-regions on the surface of the material is one of the difficulties in preparing super-amphiphilic materials. For hydrophobic carbon materials, it is often necessary to perform multi-step modification to increase the hydrophilicity of the carbon surface and adjust the ratio of hydrophilic and lipophilic functional groups on the carbon surface to achieve the preparation of super-amphiphilic carbon. CN112794303A uses cheap renewable raw materials and a small amount of ionic liquid to achieve nitrogen-doped super-amphiphilic carbon materials through one-step pyrolysis. However, the price of ionic liquids with bistrifluoromethanesulfonyl imide anions is relatively high. Although the amount of ionic liquids used is small, it is still necessary to further explore other modification methods to further reduce the preparation cost.
[0006] On the other hand, the super-amphiphilic carbon prepared in CN112794303A produces pyridine nitrogen oxides when pyrolyzing with wood powder by ionic liquid to increase the hydrophilic micro-domains on the surface of the carbon material, while elemental carbon and a small amount of fluorine element provide oleophilic micro-domains, so that a super-amphiphilic surface is constructed in the carbon material. However, after the pyridine nitrogen oxide solution absorbs water, it will decompose slowly under aerobic conditions. And the decomposition rate of pyridine nitrogen oxides will increase as the temperature rises, and this instability will cause the original super-amphiphilic carbon to become hydrophobic carbon. Therefore, it is necessary to further explore other methods to find more stable super-amphiphilic carbon materials. Summary of the invention
[0007] The technical problem to be solved by the present invention is to provide a super-amphiphilic carbon and its preparation method and application. First, the preparation cost problem is solved by changing the raw material composition and the preparation process; second, a new approach is provided for the preparation and application of super-amphiphilic carbon materials, and the stability of the prepared super-amphiphilic carbon materials is further improved.
[0008] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0009] A method for preparing super-amphiphilic carbon is characterized by comprising the following steps: mixing wood powder with an ionic liquid containing tetrafluoroborate anions, and then pyrolyzing the mixture in an inert atmosphere to obtain super-amphiphilic carbon.
[0010] Preferably, the raw material of the wood powder is hardwood and / or softwood; the hardwood is selected from at least one of poplar, beech, camphor, willow, locust, oak, pear and basswood; the softwood is selected from at least one of pine, fir and cypress.
[0011] Preferably, the ionic liquid containing tetrafluoroborate anion refers to a cation that is at least one of imidazole, pyridine, quaternary ammonium, quaternary phosphonium, pyrrole, piperidine and homologues containing the above cations and having substituents; the substituents are selected from at least one of methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl and decyl.
[0012] More preferably, the cation is methylbutylimidazole, tributylhexylphosphonium or tributylmethylammonium.
[0013] Preferably, the mass ratio of the wood powder to the ionic liquid containing tetrafluoroborate anions is 1-6:1.
[0014] Preferably, the inert atmosphere is at least one of nitrogen, argon and helium; the pyrolysis conditions are as follows: temperature is 200-450° C., and time is 2-8 hours.
[0015] The super-amphiphilic carbon is prepared according to the preparation method of the super-amphiphilic carbon.
[0016] The super amphiphilic carbon is used in the preparation of Pickering emulsion or in Pickering emulsion catalysis.
[0017] Furthermore, the super-amphiphilic carbon is mixed in an oil-water system to form a Pickering emulsion.
[0018] Furthermore, the concentration of the super-amphiphilic carbon in the Pickering emulsion is 1-5 mg mL -1 .
[0019] The positive effects of the present invention are:
[0020] The super-amphiphilic carbon prepared by the present invention has both super-hydrophilicity and super-lipophilicity, and the contact angles for water and oil such as dodecane are close to 0°. The super-amphiphilic carbon can form a Pickering emulsion in an oil-water system; and can improve the reaction efficiency of related oxidation reactions. The present invention helps to realize the formation of a stable Pickering emulsion in an oil-water system, and further improves the catalytic reaction efficiency in the emulsion.
[0021] First, the preparation cost problem is solved by changing the raw material composition and the preparation process. The price of the ionic liquid used in the present invention is about one-fifth of the price of the ionic liquid used in CN112794303A; second, a new approach is provided for the preparation of super-amphiphilic carbon materials; third, different doping elements can also expand the scope of use of super-amphiphilic carbon materials.
[0022] Fourth, the present invention uses an ionic liquid with tetrafluoroboric acid as an anion, blends it with wood powder and then pyrolyzes it. Since the boron doping in the carbon material forms a boron-oxygen bond to form a hydrophilic microdomain, the carbon and fluorine elements in the carbon material form an oleophilic microdomain, so that the carbon material exhibits super-amphiphilicity. In the present invention, boron, oxygen, carbon and nitrogen are interconnected and will not decompose under aerobic conditions, thereby further improving the stable use of super-amphiphilic carbon.
[0023] Fifth, the Pickering emulsion of the present invention can be specifically applied to catalyze the oxidation reaction of benzyl alcohol. The yield of the target product of the oxidation of benzyl alcohol (oil phase) in the water system is increased by 3 times compared with that without adding the super amphiphilic carbon. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a SEM (scanning electron microscope) image of the super-amphiphilic carbon prepared in Example 1 of the present invention;
[0025] Figure 2 The water and oil (dodecane) contact angle diagram of the super amphiphilic carbon prepared in Example 1 of the present invention;
[0026] Figure 3 This is a laser confocal fluorescence image of the Pickering emulsion formed by benzyl alcohol and water promoted by the super-amphiphilic carbon prepared in Example 1 of the present invention;
[0027] Figure 4 This is a comparison chart of the conversion rate of the target product in the oxidation reaction of benzyl alcohol in the Pickering emulsion prepared in Example 1 of the present invention compared with that without adding super amphiphilic carbon. DETAILED DESCRIPTION
[0028] The present invention is further described below with reference to the accompanying drawings and embodiments.
[0029] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.
[0030] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.
[0031] The wood powder in the following embodiments can be prepared by oneself or purchased as a commercial product, and the particle size of the wood powder is a common particle size known in the art.
[0032] Ionic liquids can be purchased or prepared according to preparation methods in other literature.
[0033] Example 1
[0034] A method for preparing a super amphiphilic carbon comprises the following steps:
[0035] 1) The wood powder raw material is poplar wood, i.e. poplar wood powder; the ionic liquid is 1-butyl-3-methylimidazolium tetrafluoroborate.
[0036] 2) The wood powder and ionic liquid in step 1) are mixed in a mass ratio of 6:1.
[0037] 3) The mixed mixture prepared in step 2) was pyrolyzed in nitrogen at 200°C for 8 hours to obtain super amphiphilic carbon, the SEM image of which is shown in FIG. Figure 1 shown.
[0038] 4) The contact angles of super-amphiphilic carbon to water and oil were measured using water and dodecane, and the results were approximately 0°, such as Figure 2 shown.
[0039] 5) Superamphiphilic carbon forms a Pickering emulsion in benzyl alcohol and water, and its laser confocal micrograph is shown in the figure below. Figure 3 As shown, the concentration of superamphiphilic carbon is 1 mg mL -1 .
[0040] 6) In the above emulsion, the yield of the target product in the oxidation reaction of benzyl alcohol was increased by 3 times compared with that without adding super-amphiphilic carbon. Figure 4 shown.
[0041] Example 2
[0042] A method for preparing a super amphiphilic carbon comprises the following steps:
[0043] 1) The wood powder raw material is oak, i.e. oak powder; the ionic liquid is tributylhexylphosphonium tetrafluoroborate.
[0044] 2) The wood powder and ionic liquid in step 1) are mixed in a mass ratio of 3:1.
[0045] 3) The mixed mixture prepared in step 2) is placed in argon gas and pyrolyzed at 350° C. for 5 hours to obtain super amphiphilic carbon.
[0046] 4) The contact angles of super-amphiphilic carbon to water and oil were measured using water and dodecane, and the results were both approximately 0°.
[0047] 5) Super-amphiphilic carbon forms a Pickering emulsion in benzyl alcohol and water. The concentration of super-amphiphilic carbon is 3 mg mL -1 .
[0048] 6) In the above emulsion, the yield of the target product in the oxidation reaction of benzyl alcohol was increased by 3 times compared with that without adding super amphiphilic carbon.
[0049] Example 3
[0050] A method for preparing a super amphiphilic carbon comprises the following steps:
[0051] 1) The raw wood powder is selected from pine wood among softwoods; the ionic liquid is selected from tributyl methyl ammonium tetrafluoroborate. 2) The wood powder and the ionic liquid in step 1) are mixed in a mass ratio of 1:1.
[0052] 3) The mixed mixture prepared in step 2) is placed in helium and pyrolyzed at 450° C. for 2 hours to obtain super amphiphilic carbon.
[0053] 4) The contact angles of super-amphiphilic carbon to water and oil were measured using water and dodecane, and the results were all approximately 0°.
[0054] 5) Super-amphiphilic carbon forms a Pickering emulsion in benzyl alcohol and water. The concentration of super-amphiphilic carbon is 5 mg mL -1 .
[0055] 6) In the above emulsion, the yield of the target product in the oxidation reaction of benzyl alcohol was increased by 3 times compared with that without adding super amphiphilic carbon.
[0056] from Figure 1 It can be seen that the super-amphiphilic carbon material prepared in Example 1 is composed of strips and some irregularly shaped carbon, and there are some fine structures on the surface of these carbon materials. The presence of these microstructures is conducive to the formation of super-amphiphilic properties of carbon materials. Through contact angle testing, it is found that the contact angles of the carbon material prepared in Example 1 for water and dodecane are approximately zero, such as Figure 2 These results show that the carbon material prepared in Example 1 exhibits super-amphiphilicity. Super-amphiphilic carbon forms a Pickering emulsion in benzyl alcohol and water, and the results of laser confocal characterization are shown in FIG. Figure 3 It can be seen that the droplet size of the water-in-oil emulsion is between 1 and 3 microns. When the Pickering emulsion is applied to the oxidation of benzyl alcohol, the conversion rate of the reactants and the yield of the target product are four times that of those without the addition of super-amphiphilic carbon. The specific comparison results are as follows Figure 4 shown.
Claims
1. A method for preparing super amphiphilic carbon, characterized in that The following steps are involved: Wood powder is mixed with an ionic liquid containing tetrafluoroborate anions, and then pyrolyzed in an inert atmosphere to obtain super amphiphilic carbon; the pyrolysis conditions are as follows: temperature is 450°C, and time is 2 to 8 hours.
2. The method for preparing super-amphiphilic carbon according to claim 1, characterized in that: The raw material of the wood powder is hardwood and / or softwood; the hardwood is selected from at least one of poplar, beech, camphor, willow, locust, oak, pear and basswood; the softwood is selected from at least one of pine, fir and cypress.
3. The method for preparing super-amphiphilic carbon according to claim 1, characterized in that: The ionic liquid containing tetrafluoroborate anion refers to a cation that is at least one of imidazole, pyridine, quaternary ammonium, quaternary phosphonium, pyrrole, piperidine and homologues containing the above cations and having substituents; the substituents are selected from at least one of methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl and decyl.
4. The method for preparing super-amphiphilic carbon according to claim 3, characterized in that: The cation is methylbutylimidazole, tributylhexylphosphonium or tributylmethylammonium.
5. The method for preparing super-amphiphilic carbon according to claim 1, characterized in that: The mass ratio of the wood powder to the ionic liquid containing tetrafluoroborate anions is 1-6:
1.
6. The method for preparing super-amphiphilic carbon according to claim 1, characterized in that: The inert atmosphere is at least one of nitrogen, argon and helium.
7. The super-amphiphilic carbon prepared by the method for preparing the super-amphiphilic carbon according to any one of claims 1 to 6.
8. The use of the super-amphiphilic carbon according to claim 7 in the preparation of Pickering emulsion or in Pickering emulsion catalysis, characterized in that: The Pickering emulsion was applied to the oxidation of benzyl alcohol.
9. The use of the super-amphiphilic carbon according to claim 8 in the preparation of Pickering emulsion or in Pickering emulsion catalysis, characterized in that: The super-amphiphilic carbon is mixed in an oil-water system to form a Pickering emulsion.
10. Use of the super-amphiphilic carbon according to claim 8 in preparing a Pickering emulsion or in Pickering emulsion catalysis, characterized in that: The concentration of superamphiphilic carbon in the Pickering emulsion is 1-5 mg mL -1 .
Citation Information
Patent Citations
Hydrophilic oil absorption cotton
CN104383899A
Super-amphiphilic porous membrane material and preparation method and application thereof
CN107174972A
Amphiphilic Janus structure graphene-based aerogel and preparation method thereof
CN108439373A
Surface amphiphilic nano-molybdenum disulfide hydrogenation catalyst and preparation method and application thereof
CN105435818A
Super-amphiphilic carbon as well as preparation method and application thereof
CN112794303A